A novel miniature transposon-like element discovered in the coding sequence of a gene that encodes for 5-formyltetrahydrofolate in wheat - Katherine Domb; Danielle Keidar-Friedman; Khalil Kashkush (BMC Plant Biology, 2019)
Abstract Background Transposable elements (TEs) comprise over 80% of the wheat genome and usually possess unique features for specific super-families and families. However, the role of TEs in wheat evolution and reshaping the wheat genome remains largely unclear. Results In this study, we discovered a miniature (307 bp in length) TE-like sequence in exon 6 of a gene that encodes for 5-formyltetrahydrofolate, in two accessions of wild emmer wheat (T. turgidum ssp. dicoccoides) and has interfered with the gene translation by creating a shorter reading frame as a result of a stop codon. The sequence that was termed Mariam, does not show any structural similarity to known TEs. It does not possess terminal inverted repeats (TIRs) that would allow us to assign this element to one of the TIR DNA super-families, and it does not possess characteristic features of SINE, such as a Pol-III promotor or a poly-A tail. In-silico analysis of five publicly available genome drafts of Triticum and Aegilops species revealed that Mariam element appears in a very low copy number (1–3 insertions) in diploid wheat species and ~ 12 insertions in tetraploid and hexaploidy wheat species. In addition, Mariam element was found to be unique to wheat, as it was not found in other plant genomes. The dynamic nature of Mariam in the wheat genome was assessed by site-specific PCR analysis and revealed that it retained activity in wild emmer populations in a population-specific manner. Conclusions This study provides additional insight into the evolutionary impact of TEs in wheat.